The return - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Amish beginnings novel., 2017)
As the Amish settle in America, Tessa wishes Hans would notice her. When tragedy strikes--close to home and close to her heart--she discovers the cost of true love.